Determination of oleanolic acid in human plasma and its association with olive oil intake in healthy Spanish adults within the EPIC Spain cohort study. Issue 8 (20th March 2017) - Buckland, Genevieve; Pastor, Antoni; Lujan‐Barroso, Leila; Gonzalez, Carlos Alberto; Travier, Noemie; Amiano, Pilar; Huerta, José María; Agudo, Antonio; Navarro, Carmen; Chirlaque, María Dolores; Sánchez, Maria‐José; Rodríguez‐Barranco, Miguel; et al.
Abstract : Oleanolic acid (OA) is an important minor compound in olive oil with potentially beneficial health effects. This study determined concentrations of OA in blood in the general population for the first time and found a low‐to‐moderate link between blood OA and olive oil intake. Whether OA concentrations in blood are a good marker of olive oil consumed needs to be further clarified. Abstract : Scope: Oleanolic acid (OA) is an important triterpenic compound found in olive oil, however little is known about its concentrations in human plasma. We aimed to determine plasma OA levels in a healthy Spanish population and compare them with estimates of dietary olive oil intake. Methods and results: The final study sample included 141 individuals randomly selected from the European Prospective Investigation into Cancer and Nutrition Spanish cohort. Dietary olive oil intake was estimated using validated dietary history questionnaires. OA concentrations were determined in plasma (from the participants' stored blood samples) using a HPLC‐MS method. Correlation coefficients between OA and olive oil intake were calculated, adjusting for center; sex; age; consumption of olives, apples, grapes, and red wine; and fasting state. The mean OA concentration in olive oil nonconsumers was 0.72 ng/mL (SD 0.82), while in the high olive oil intake group it was 1.32 ng/mL (SD 1.14). The fully adjusted partial Spearman correlations coefficients reached 0.36 ( p ‐value < 0.001) overall, varying minimally by sex and fasting state. Conclusion: This is the first study providing steady‐state concentrations of triterpenes in humans. The results show that there was low‐to‐moderate correlation between OA concentrations and olive oil intake in this population.